Pre-trial investigation in the de-occupied territories: normative regulation and prospects for implementation - T. H. Fomina (Bulletin of Kharkiv National University of Internal Affairs)
The state of normative regulation of the pre-trial investigation procedure was studied, as well as the prospects for its implementation after the de-occupation of Ukrainian territories were clarified. It was emphasized that the raised issue requires qualitative discussion by representatives of various institutions of criminal justice. It is important in this direction to build effective algorithms for pre-trial investigation bodies, the prosecutor’s office, the court, which cannot be implemented without the introduction of new legislative initiatives.